Manipulation of colony environment modulates honey bee aggression and brain gene expression. (9th October 2013) - Rittschof, C. C.; Robinson, G. E.
Abstract : The social environment plays an essential role in shaping behavior for most animals. Social effects on behavior are often linked to changes in brain gene expression. In the honey bee ( Apis mellifera L.), social modulation of individual aggression allows colonies to adjust the intensity with which they defend their hive in response to predation threat. Previous research has showed social effects on both aggression and aggression‐related brain gene expression in honey bees, caused by alarm pheromone and unknown factors related to colony genotype. For example, some bees from less aggressive genetic stock reared in colonies with genetic predispositions toward increased aggression show both increased aggression and more aggressive‐like brain gene expression profiles. We tested the hypothesis that exposure to a colony environment influenced by high levels of predation threat results in increased aggression and aggressive‐like gene expression patterns in individual bees. We assessed gene expression using four marker genes. Experimentally induced predation threats modified behavior, but the effect was opposite of our predictions: disturbed colonies showed decreased aggression. Disturbed colonies also decreased foraging activity, suggesting that they did not habituate to threats; other explanations for this finding are discussed. Bees in disturbed colonies also showed changes in brain gene expression, some of which paralleled behavioral findings. These results show that bee aggression and associated molecular processes are subject to complex social influences . Abstract : Honey bees exposed to chronic predator disturbance show decreased aggression and changes in brain gene expression.